Molecular Mechanism and Targets of the Antimicrobial Activity of Metal Nanoparticles - (:unkn) unknown (BENTHAM SCIENCE PUBL LTD, 2015)
The emergence of multi-resistant bacteria to drugs is recognized as a major cause of the increasing number of deaths in hospitals. Killing these bacteria require multiple expensive drugs that can have side effects. Metal nanoparticles may provide a new strategy to combat them. Due the antimicrobial and antiviral properties, nanoparticles (NPs) have outstanding biological properties that can be handled properly for desired applications. This review presents antibacterial and antiviral activity of metal NPs, including the molecular mechanisms by which NPs annihilate multidrug-resistant bacteria.
Keywords: Antibacterial; Antiviral; Drug-multiresistant bacteria; Molecular mechanism; SILVER NANOPARTICLES; ANTIBACTERIAL ACTIVITY; ESCHERICHIA-COLI; GOLD NANOPARTICLES; MEDIATED TOXICITY; MGO NANOPARTICLES; DOPED TIO2; ZNO; COPPER; NANOMATERIALS